Anti-Inflammatory Effect of Musa acuminata Stem - Apriasari, Maharani Laillyza; Pramitha, Selviana Rizky; Puspitasari, Dewi; Ernawati, Diah Savitri (European Journal of Dentistry, 2020)
Objective This study was designed to assess the anti-inflammatory effect of Musa acuminata through the expression of tumor necrosis factor-α (TNF-α) and nuclear factor kappa β (NF-κB) after 3 days of application of Musa acuminata stem extract (MASE) gel on oral mucosal wound.Materials and Methods An experimental study with post-test only control group design was conducted. Twenty male Rattus norvegicus (Wistar) were injured on their left buccal mucosa and treated three times a day with MASE gel of varying concentrations: 0% (as control), MASE 25%, MASE 37.5%, and MASE 50%. On day 3, a biopsy was performed on each mucosal wound for later immunohistochemical analysis for the expressions of TNF-α and NF-κB.Results The highest expression of TNF-α was observed in the control group (13.20 ± 1.79), while the lowest was in the treatment group using 50% MASE (6.40 ± 1.14). Meanwhile the comparison between treatment groups did not highlight any significant difference (p > 0.05). The highest expression of NF-κB was observed in the control group (13.20 ± 1.30), whereas the lowest was in the treatment group using MASE 50% (6.40 ± 1.14). NF-κB was significantly lower in the treatment group using MASE 50% when compared with other treatment groups (p < 0.05).Conclusion Application of MASE on mucosal wound reduces the expression of TNF-α and NF-κB at all concentrations. The anti-inflammatory effect of MASE 50% was the strongest one.
Keywords: Musa acuminata; anti-inflammation; TNF-α; NF-κB